Diversifikasi Minyak Kenanga Melalui Penyulingan Uap Terfraksinasi. - Achmad Moestafa; Endang Djubaedah; Enjang Ahdiansyah (Jurnal Kimia dan Kemasan, 2000)
An attempt to diversify Java Cananga Oil (Canangium odoratum Bail) into several grades like Ylang-ylang oil (Canangium odoratum genuina) to gain a better price in the world market had been conducted. In this experiment the distillation of cananga oil was divided into six fractions, each fraction four hours, namely the first four hours fraction, the second four hours and so on up to six fractions of four hours distillation. Each fraction wascollected and analyzed for its ester value and its refractive indices. From the experiment it was found that the first fraction has the highest ester value namely 61. 68, the 2nd fraction to the 6 st fraction were 45.81; 38.02; 26.92 and 26.01 respectively. From the result it was found that the first fraction has the highest ester value (61. 68), which is within the range of ylang-ylang oil grade 3. Base on the results above Java Cananga Oil might be grouped into four grades, namely the Super cananga oil has minimum 60 ester value, grade 1 has 45 to 60, grade 2 has 35 to 45 and grade 3 has 20 to 35.